2017
DOI: 10.1186/s12944-017-0639-7
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism in the hepatic protein response to a moderate trans fat diet in senescence-accelerated mice

Abstract: BackgroundAging is characterized by increases in inflammation and oxidative stress, conditions that are exacerbated by environmental factors such as diet. In this study, we investigated the effects of a trans-fatty acid (TFA) diet on the liver in adult (25 wk) and old (60 wk) senescence-accelerated mice (SAMP8 strain) of both sexes. Our goal was to assess the effects of the diet on protein markers of inflammation and oxidative stress in the liver.MethodsMale and female mice were placed on life-long diets conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…This is also true for the soda-fed rats, the male animals had an increase in thoracic circumference, but a decrease was observed in female animals. Sexual dimorphism has been well reported in literature in response to diet treatment in rats [ [48] , [49] , [50] ] This study suggests that male animals seem to respond more to diet treatment, in this case a HPD-soda diet.…”
Section: Discussionsupporting
confidence: 55%
“…This is also true for the soda-fed rats, the male animals had an increase in thoracic circumference, but a decrease was observed in female animals. Sexual dimorphism has been well reported in literature in response to diet treatment in rats [ [48] , [49] , [50] ] This study suggests that male animals seem to respond more to diet treatment, in this case a HPD-soda diet.…”
Section: Discussionsupporting
confidence: 55%
“…Thus, it has been reported that during perinatal mouse lung development, females show higher GPx1 mRNA transcription levels than males, suggesting females may be better protected against oxidative stress [ 94 ]. In support of this view, mice fed a moderate trans-fat diet the hepatic expression of lipogenic, and antioxidant proteins were higher in female than in male mice [ 95 ]. In our results, it is evident that the placentas and the fetal liver of males and females in the control group differ in the concentrations of oxidative stress biomarkers and the activity of antioxidant enzymes, and that both the placenta and fetal liver of females from obese mothers exhibited a greater response than males to counteract the harmful effects of the intrauterine environment to which they are exposed.…”
Section: Discussionmentioning
confidence: 99%
“…Some [3][4][5][6] though not all [59][60][61][62] controlled dietary intervention studies suggest that trans fat intake may result in higher levels of circulating proinflammatory markers. Preclinical studies also suggest that trans fatty acids could promote de novo fatty acid synthesis [63,64].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the effects of trans fatty acids on breast cancer risk may be mediated through FAS expression and that trans fats may increase the risk of a FAS high breast cancer subtype. This hypothesis is supported by mechanistic studies in mice, where a diet high in trans fat produced a 2- to 3-fold increase in mRNA of FAS [ 63 , 64 ] and a 2-fold increase in mRNA of sterol regulatory element binding protein (SREBP)-1 [ 64 ], a transcription factor that upregulates fatty acid synthesis [ 65 ]. Breast tumor overexpression of FAS has also long been recognized as an indicator of poor clinical prognosis [ 66 ], lending greater public health importance to the hypothesis that trans fatty acids may increase the risk of breast cancers with high FAS expression.…”
Section: Discussionmentioning
confidence: 99%